2013
DOI: 10.2196/resprot.2327
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Design for Community-Based Physical Activity Programs for Socially Disadvantaged Groups: Communities on the Move

Abstract: BackgroundAs interventions are not yet successful in substantially improving physical activity levels of low socioeconomic status groups in the Netherlands, it is a challenge to undertake more effective interventions. Participatory community-based physical activity interventions such as Communities on the Move (CoM) seem promising. Evaluating their effectiveness, however, calls for appropriate evaluation approaches.ObjectiveThis paper provides the conceptual model for the development of a context-sensitive mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 33 publications
0
33
0
1
Order By: Relevance
“…Also, it is suggested that more effective programs can be made by further alignment of interventions to the targeted population [9e11]. Therefore, it is necessary to identify ingredients that make interventions more effective in encouraging adolescents to become more physically active [12].…”
mentioning
confidence: 99%
“…Also, it is suggested that more effective programs can be made by further alignment of interventions to the targeted population [9e11]. Therefore, it is necessary to identify ingredients that make interventions more effective in encouraging adolescents to become more physically active [12].…”
mentioning
confidence: 99%
“…It is evident that evaluating these types of complex interventions is conceptually challenging. Using the traditional randomized controlled trial (RCT) approach is not feasible because of its lack of in-depth examination of the social, cultural, and organizational factors that could influence outcomes [ 80 ]. In addition, it is almost impossible to use randomization procedures within the real life situations in which CBR programs are implemented [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the traditional randomized controlled trial (RCT) approach is not feasible because of its lack of in-depth examination of the social, cultural, and organizational factors that could influence outcomes [ 80 ]. In addition, it is almost impossible to use randomization procedures within the real life situations in which CBR programs are implemented [ 80 ]. Finally, the information gathered through an RCT does not allow the capturing of the interactions between the individuals and their social and physical environments [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are a few international studies on physical activity interventions guided by a CBPR approach [28][29][30][31]. Moreover, studies evaluating CBPR based intervention using multiple health evaluation methods longitudinally [26] are sparse.…”
Section: Introductionmentioning
confidence: 99%